NUTRITIONAL STATE AND BODY FAT CONTENT FROM PUBLIC SCHOOL STUDENTS FROM THE CITY OF MARINGÁ/PR/BRAZIL. (Fiep Bulletin - online, 2014)
The objective of the present study was to evaluate the nutritional state and the body fat content from children and pre-adolescent in a public school from the city of Maringá, Paraná, Brazil. They were part of the study 444 children from 1st to 4th grade, of both gender, with age between 7 to 12 years, being 223 of male gender (50.2%) and 221 of female gender (49.8%). The classification was made from the determination of Body Mass Index (BMI). The nutritional classification system proposed by Conde and Monteiro (2006) was used, because it was specifically developed to Brazilian children and adolescent and also because it includes the classification of low weight, just like the classification of overweight and obesity. The body fat percent was estimated by predictives equations proposed by Slaughter et al (1988). The population's mean BMI was 17.6 Kg/m2 and the mean body fat content was 20.9%. In spite of finding the majority of children (68.1%) within normality pattern, it was observed that 27.8% from boys and 33.5% from girls were found with weight excess, showing an expressive value of weight excess and obesity in both gender. Considering the age group studied, the school is a more adequate place to intervention, where educatives programs about eating habits and physics activity practice related to a healthy life style have to be emphasized since the pre school fase in expectation to acquire a reduction on the incidence of overweight and obesity in this population.
Keywords: Overweight; Obesity; School Students